Analisis Regresi Kecepatan Angin Terhadap Daya Turbin Angin Jenis VAWT Tipe Darrieus-Savonius - Luthfi - Hakim; Achmad Rijano; Mochamad Muzaki (Polinema Press, Politeknik Negeri Malang, 2018)
The Darrieus-Savonius (DS) wind turbine has been widely developed with the aim of improving turbine performance that has been designed. DS wind turbine is a combination of two type of wind turbines, that is Darrieus and Savonius turbine, both turbines are intentionally developed In order to get self-starting on turbine Savonius with low wind speed and able to extract the speed of engine into energy well at high wind speed through Cherrie Darrieus. This study was conducted to analyze the performance of the DS turbine in the wind speed to be energized through the turbine rotation and power to be generated. The DS wind turbine is designed to start rotating at a speed of 8 m/s in velocity of wind, meanwhile the maximum power generated by turbine is 48,23 Watts.